Oral health status among patients treated with fixed orthodontic appliance at different time intervals (Mustansiria Dental Journal, 2019)
Background: Fixed orthodontic appliance considered a risk factor that effect oralhealth status. Aims of this study were evaluation of oral hygiene, gingival healthand caries experience among patients with fixed orthodontic appliance atdifferent time intervals of treatment.Material & Methods:- 32 patients (24 female and 8 male) included in this study andthey underwent clinical examination plaque, calculus, gingival health and cariesexperience by using Loe, 1967, Green and vermillion, 1960 and WHO, 1987indices at four time intervals: 2-3 weeks after appliance insertion, 2 months, 4months, 6 months. The statistical analysis of data was by using statisticalPackage for social Sciences (SPSS version 18).Results:- The means of all variables examined increased during six months oforthodontic treatment with high significant difference during visits. 49.6% ofpatients developed new caries lesions after six months of treatment.Conclusion:- Patients underwent orthodontic treatment at high risk for developingoral health problems.